THE POTENTIAL OF PEDAGOGICAL VOLUNTEERING IN THE PROFESSIONAL TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS FOR EDUCATIONAL ACTIVITIES - BYHAR, Anna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
In this article, through theoretical analysis of scientific research, regulatory documents, methodological literature, and programme-methodological support of the educational process in higher education institutions, issues related to the preparation of future primary school teachers for educational activities have been identified: the goals of professional teacher training lack a focus on forming the foundational elements of a personal-professional educator’s stance; the content and technologies for preparing future primary school teachers for educational activities are presented fragmentarily in educational programs, with minimal coverage; the requirements for professional training outcomes in the field of education, as outlined in the professional standards for positions like “Primary School Teacher of General Secondary Education,” “Secondary Education Teacher,” and “Primary Education Teacher (with a junior specialist diploma)” need specification and clarification based on real-world educational practices, employer requirements, and up-to-date knowledge of the contemporary child's world. This article aims to theoretically study various volunteer practices in modern society and identify the potential of voluntary activities for future primary school teachers to gain educational experience. It is argued that, in such a situation, attention should be paid to various ways of integrating formal and non-formal education, which involve voluntary, independent, conscious, professionally oriented student activity in extracurricular activities, particularly in professional volunteer work. It has been established that professional volunteer work involves a transition from academic-cognitive to independent professional activities, serving as a means of student self-realisation and, under appropriate conditions, developing professional competences. Pedagogical volunteering is considered a voluntary activity involving students' voluntary and unpaid participation in addressing, educating, and teaching children. It is generalised that pedagogical volunteering, as a means of preparing future primary school teachers for educational activities, includes voluntary educational activities by student-teachers with children in extracurricular time through independently developed educational projects created considering the student cohort, sociocultural conditions, and resources of social partners.